HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP PEREMPUAN TERHADAP PENYAKIT INFEKSI MENULAR SEKSUAL - Rahmawati, Rahmawati; Noorma, Nilam; Marwiyah, Nila; Yanti, Entin Srihadi; Yanti, Lilis Candra (Ensiklopedia of Journal, 2024)
Sexually transmitted infections (STIs) are one of the most widespread and dangerous infectious diseases. More than 30 types of pathogens can be transmitted through sexual intercourse with clinical manifestations varying by sex and age. STIs rank in the top 10 reasons for seeking treatment in many developing countries, and the costs incurred can affect household income. The purpose of the study was to determine the relationship between the level of knowledge and attitudes of women towards sexually transmitted diseases. This study was conducted in the working area of the Tandun 1 Health Center with a sample of 92 respondents. The research design used was descriptive correlation using a research tool in the form of a questionnaire. The analysis used was frequency distribution and kai squared to analyze the relationship between variables. The results of this study indicate that there is a significant relationship between the level of knowledge (p value = 0.000 < α = 0.05) and attitude (p value = 0.000 < α = 0.05) with the incidence of sexually transmitted infections in the working area of Tandun 1 Health Center. The study recommends that the community of the Tandun 1 Health Center working area be able to increase knowledge about STIs and good attitudes to prevent STIs.Keywords: Sexually transmitted infections, knowledge, attitude